Application of the guided inquiry method to improve science literation in state 6 Banda Aceh middle school students - Debby Pratiwi; Ismul Huda; Andi Ulfa Tenri Pada; Cut Nurmaliah; Muhibbuddin Muhibbuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
The purpose of this research is to study the Guided Question method to improve students' literacy skills in SMP Negeri 6 Banda Aceh. This study uses quantitative, experimental research methods that are of the type of Pretest-Posttest Control Group Design. Data collection consists of pretest and posttest data on scientific literacy on the application of the Guided Inquiry method. Analysis of literacy data is calculated by using the Independent Sample T-test and the Mann-Withney U test. Data obtained from the test of two different parametric means by paired t-test (Independent Sample T-test) class posttest Research Method Inquiry with the Conventional Method class with grade significance of 0.00 considers differences in posttest perception Guided Inquiry Method with Conventional Method classes and two mean difference test with non-parametric test (Mann-Whithney test) n-gain score of research with n-gain control support significance of 0.04 with a significance level of 0 , 05 shows a difference of two on average because it is less than 0.05 or there is an increase in students' literacy skills in the material structure and function of planting with learning using the Guided Inquiry method and increasing learning competence in learning using Conventional methods. The experimental class with initial ability 27.34 and 51.70 final ability while the control class with initial ability 30.80 and 39.17 final ability with an increase in experimental class by 45% and control class 16%. Conclusions agreed that the application of the Inquiry Learning method could significantly increase literacy in SMP Negeri 6 Banda Aceh.Keywords: Guided Inquiry Method, Science Literacy Pelaksanaan penelitian ini bertujuan untuk mengetahui metode Guided Inquiry dapat meningkatkan kemampuan literasi sains siswa di SMP Negeri 6 Banda Aceh. Penelitian ini dengan pendekatan kuantitatif, dengan Experimental sebagai metode penelitiannya yang berjenis Pretes-Posttest Control Group Design. Pengumpulan data berupa data pretes dan posttest literasi sains terhadap penerapan metode Guided Inquiry. Analisis data literasi sains dihitung dengan uji Independent Sample T-test dan uji Mann-Withney U. Data yang didapat dari uji perbedaan dua rerata parametrik dengan uji-t berpasangan (Independent Sample T-test) posttes kelas Metode Guided Inquiry dengan kelas Metode Konvensional dengan taraf signifikansi 0,00 bermaksudkan bahwa adanya perbedaan posttest Metode Guided Inquiry dengan kelas Metode Konvensional dan uji perbedaan dua rerata dengan uji non-parametrik (uji Mann-Whithney) skor n-gain eksperimen dengan n-gain kontrol memiliki signifikansi 0,04 dengan taraf signifikansi 0,05 menunjukkan adanya perbedaan dua rata-rata karena kurang dari 0,05 atau adanya peningkatan kemampuan literasi sains siswa pada materi struktur dan fungsi tumbuhan dengan pembelajaran menggunakan metode Guided inquiry dan memiliki perbedaan nyata peningkatan pada kelas pembelajaran menggunakan metode Konvensional. Kelas eksperimen secara berurutan kemampuan awal 27,34 dan 51,70 kemampuan akhir sedangkan kelas kontrol memiliki kemampuan awal 30,80 dan 39,17 kemampuan akhir dengan peningkatan kelas eksperimen sebesar 45% dan kelas kontrol 16%. Kesimpulan menyatakan penerapan metode Pembelajaran Guided Inquiry dapat meningkatkan literasi sains secara signifikan di SMP Negeri 6 Banda Aceh.Kata Kunci: Metode Guided Inquiry, Literasi Sains